2006
DOI: 10.1158/1535-7163.mct-06-0327
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of different dihydropyrimidine dehydrogenase gene single nucleotide polymorphisms on 5-fluorouracil tolerance

Abstract: Purpose: Although single nucleotide polymorphisms (SNP) of the dihydropyrimidine dehydrogenase gene (DPYD) have been reported, which affect enzyme activity and the severity of 5-fluorouracil (5-FU) toxicity, no pretherapeutic detection has thus far been developed. We investigated 22 DPYD gene SNPs, their respective incidence, their link with grade 3 to 4 toxic side effects, and their management in practice: 9 were looked for in 487 patients, whereas 13 others were investigated in 171 patients. Patients and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
2
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(162 citation statements)
references
References 40 publications
5
148
2
7
Order By: Relevance
“…Its allele frequency in Japanese (0.029 in this study) and Taiwanese (0.022) (Hsiao et al 2004) was much lower than that in (Seck et al 2005;Morel et al 2006).…”
Section: Ethnic Differences In Distributions Of Dpyd Snps and Haplotypescontrasting
confidence: 59%
See 1 more Smart Citation
“…Its allele frequency in Japanese (0.029 in this study) and Taiwanese (0.022) (Hsiao et al 2004) was much lower than that in (Seck et al 2005;Morel et al 2006).…”
Section: Ethnic Differences In Distributions Of Dpyd Snps and Haplotypescontrasting
confidence: 59%
“…For example, IVS14 + 1G[A (*2) (van Kuilenburg 2004), 295_298delTCAT (Phe100SerfsX15, *7) (Seck et al 2005), 1679T[G (Ile560Ser, *13) (CollieDuguid et al 2000;Morel et al 2006) 2846A[T (Asp949Val) (Seck et al 2005;Morel et al 2006), all of which are associated with decreased DPD activities, are detected in Caucasians with allele frequencies of 0.01-0.02, 0.003, 0.001 and 0.006-0.008, respectively. However, none of them were detected in our Japanese samples, while 1003G[T (Val335Leu, *11) and 2303C[A (Thr768Lys) have been found only in Japanese, indicating that variations with clinical relevance do not overlap between Caucasians and Japanese.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 These SNPs are associated with severe DPD deficiency and a potential life-threatening toxicity under a 5-FU regimen.…”
Section: Genotypingmentioning
confidence: 99%
“…58,59 The most known DPD SNPs related to grade 3 to 4 toxicities are found on chromosome 1p. They mainly consist of the polymorphisms IVS14 þ 1G-A, 2846A-T, 1679T-G and 85T-C. 60 Recently, a new SNP mutation was found at exon 5 of the DPD gene (464T-A) and was associated with a life-threatening toxicity. 44,61 It has also been reported that the TS/DPD and TP/DPD ratios are of prognostic significance in CRC.…”
Section: Genetic Alterations In Crcmentioning
confidence: 99%